Ants, bees, and other social insects - Hirschmann, Kris, 1967- (New York : Scholastic, 2004)
Explore the world of social insects, with an emphasis on ants and bees.
Includes index.
"This edition is only available for distribution through the school market"--P. [4] of cover.
Keywords: Insect societies -- Juvenile literature; Bees -- Juvenile literature; Ants -- Juvenile literature